2017
DOI: 10.1016/j.icarus.2017.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Small-scale density variations in the lunar crust revealed by GRAIL

Abstract: Data from the Gravity Recovery and Interior Laboratory (GRAIL) mission have revealed that ~98% of the power of the gravity signal of the Moon at high spherical harmonic degrees correlates with the topography. The remaining 2% of the signal, which cannot be explained by topography, contains information about density variations within the crust. These high-degree Bouguer gravity anomalies are likely caused by small-scale (10's of km) shallow density variations. Here we use gravity inversions to model the small-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 55 publications
2
28
0
Order By: Relevance
“…However, the random background variations in the gravity gradients are of comparable magnitude to the signal of interest at the rings. These background variations are not noise in the data, but instead reveal seemingly random, small-scale density anomalies within the upper crust (Jansen et al, 2017). This variability poses a challenge to any study of small-scale (<100 km) subsurface structures using the GRAIL data.…”
Section: Gravity Gradient Profilesmentioning
confidence: 97%
See 2 more Smart Citations
“…However, the random background variations in the gravity gradients are of comparable magnitude to the signal of interest at the rings. These background variations are not noise in the data, but instead reveal seemingly random, small-scale density anomalies within the upper crust (Jansen et al, 2017). This variability poses a challenge to any study of small-scale (<100 km) subsurface structures using the GRAIL data.…”
Section: Gravity Gradient Profilesmentioning
confidence: 97%
“…However, this limiting resolution nevertheless resulted in loss of signal from the crust-mantle interface at shorter wavelengths. Maps of the residual gravity anomaly not included in the GRAIL global crustal thickness models show anomalies in the range of ±40 mGal in the vicinity of the major basins (e.g., Figure 1b of Jansen et al, 2017). As a lower…”
Section: Crustal Thickness Modelingmentioning
confidence: 98%
See 1 more Smart Citation
“…Lunar subsurface structures have also been recovered using three‐dimensional (3D) density inversion methods based on the Li and Oldenburg (, ) algorithm (Jansen et al, ; Liang et al, ). Jansen et al () used this algorithm in Cartesian coordinates to model the small‐scale 3D density variations in the lunar crust ranging from 100 to 200 kg/m 3 . Although mafic intrusions can explain most of the variations in the density anomalies, Jansen et al () also suggested that they can equally be explained by variations in rock porosity.…”
Section: Introductionmentioning
confidence: 99%
“…Jansen et al () used this algorithm in Cartesian coordinates to model the small‐scale 3D density variations in the lunar crust ranging from 100 to 200 kg/m 3 . Although mafic intrusions can explain most of the variations in the density anomalies, Jansen et al () also suggested that they can equally be explained by variations in rock porosity. Liang et al () modified the 3D density inversion of Li and Oldenburg (, ) and used it to resolve the subsurface density structure of the lunar crust, including mass concentration and lunar basins, in spherical coordinates.…”
Section: Introductionmentioning
confidence: 99%